Spiritual Growth or Decline and Meaning-Making as Mediators of Anxiety and Satisfaction with Life During Religious Struggle - Zarzycka, Beata (Journal of religion and health, 2019)
A number of studies have demonstrated links between spiritual struggles and health problems. As yet, however, only a few studies have investigated what makes religious struggle a source of mental problems or a source of well-being. We determined whether spiritual growth, spiritual decline, and meaning-making mediated the relationship between religious struggle and anxiety and satisfaction with life. Of the 180 respondents, 92 were women, and mean (SD) age was 24 (8.2) years. Each respondent completed the Religious and Spiritual Struggles Scale, the Meaning-Making Scale, the Spiritual Transformation Scale, the State-Trait Anxiety Inventory, and the Satisfaction with Life Scale. Religious struggle correlated positively with anxiety and negatively with satisfaction with life. Spiritual growth mediated the relationship between moral and demonic struggle with satisfaction with life, and spiritual decline mediated the relationship between demonic, moral, and interpersonal struggle with anxiety. Finally, meaning-making mediated the relationship between religious doubt and satisfaction with life.